The effect of xylene on histology of spleen in female adolescent sprague dawley rat - Mohd Aidi, A.M.; Hasmah, A.; Nurul Aiman, M.Y.; Yasrul Izad, A.B. (2018)
Introduction: Xylene is an aromatic hydrocarbon that is widely used in industries such as rubber and printing. The spleen tissue contains red pulp and white pulp and lymphocytes that serve as body defense mechanism for foreign and invasion of toxic substances. We hypothesize that xylene exposure might affect cellular morphology of spleen in the white pulp. Quantitative analysis on the size of the white pulp of spleen after the exposure to xylene was done. Method: Twelve Sprague Dawley female rats (n=12) were randomly divided into two groups; control group and xylene group. Rats were sacrificed and spleen were removed for to histological studies. Cross sections of spleen were stained by haematoxylin and eosins to analyze the changes of white pulp on the spleen. The white pulp marginal zone and germinal center were compared within groups. Results: Image captured showed that xylene exhibits cause an increase in the size of white pulp of spleen indicates an increase in the number of lymphocytes. There were significant difference between the control group and the xylene exposure group. The median size of the white pulp of spleen in the control group was 80361.42µm and xylene group is 113047.78µm. Conclusion: In conclusion, xylene increases the size of the white pulp of spleen in female Sprague-Dawley rat thus increases the number of lymphocytes.